PENGARUH MODEL PEMBELAJARAN LOK-R TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA PEMBELAJARAN SEJARAH KELAS X SMA NEGERI 14 PEKANBARU - Mesrayani, Ade; Suroyo; Ananda Hasibuan, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of applying the LOK-R learning model on students' cognitive learning outcomes in history lessons for class X at SMA Negeri 14 Pekanbaru. The research uses a quasi-experimental method with a Pre-test–Post-test Non-Equivalent Control Group design. The instruments used are learning outcome tests in the experimental and control classes. The research results show that the LOK-R learning model can be effectively applied in history teaching and has a significant impact on students' learning outcomes. This is evidenced by the t-test with a Sig. (2-tailed) value of 0.00 < 0.05. Additionally, the N-Gain value of the experimental class is 0.7024 (70%, high category), thus the LOK-R model is proven to effectively improve independent learning outcomes and is suitable for implementation in schools.